Switchable photovoltaic window for on-demand shading and electricity generation. (15th January 2022) - Götz-Köhler, Maximilian; Banik, Udayan; Meddeb, Hosni; Neugebohrn, Nils; Berends, Dennis; Gehrke, Kai; Vehse, Martin; Agert, Carsten
Highlights: Solar cells with switchable transparency allow for on-demand shading and electricity generation. The PV energy potential for switchable PV windows is estimated for various climatic regions. Switching scenarios for PV windows installed in commercial and residential buildings are analyzed. Temperature distribution, emissivity and transparency of switchable PV window in double glazing are studied. Abstract: A next step in the development of transparent photovoltaic windows would be to introduce a switching mechanism that allows the user to switch the window between a transparent and an opaque state as desired to generate electricity and shade the building interior. In this work, we investigate a switchable photovoltaic window consisting of the combination of a semitransparent germanium solar cell and a gasochromic switchable magnesium mirror in a double glazing. We analyze the average visible transmittance (AVT) and spectral emissivity (ε) of the device in the transparent (AVT = 18%, ε = 0.27) and light harvesting states (AVT = 1%, ε = 0.06). The thermal and electrical performance of the switchable solar cell is studied under varied solar irradiance. The experimental results are used to model the annual electricity generation of a switchable photovoltaic window in different climate regions under different switching scenarios, based on datasets from the Photovoltaic Geographical Information System (PV-GIS). The model suggests that especially in Mediterranean regions, switchable transparent photovoltaic windows with an efficiency of 2% can be a promising step to combine on-demand shading with electricity generation. Moreover, it shows that to generate more than 20 kWh/m 2 of electricity per year with this technology, the switching must be additionally coupled to the occupancy of the indoor spaces. Our model is applicable to other switchable PV technologies for evaluation purposes and to estimate ideal use cases.